OP0018 Epigenetic Study of Advanced Ankylosis in Patients with Ankylosing Spondylitis. (10th June 2014) - O'Rielly, D.D.; Zhang, Y.; Al-Ghanim, N.; Ardern, R.; Munn, A.; Hamilton, S.; Bricknell, R.; Zhai, G.; Rahman, P.
Abstract : Background: Ankylosing spondylitis (AS) is an inflammatory spinal disease characterized by ankylosis of the spine. A subset of patients develops significant ankylosis resulting in mobility issues. Objectives: To determine if epigenetic modifications may account for differences in the degree of ankylosis of the axial spine in ankylosing spondylitis. Methods: AS patients satisfying the New York criteria with advanced ankylosing (characterized clinically with spinal flexion) and radiographically with at least 4 continuous ankylosed vertebrae were categorized as advanced ankylosis. Control AS patients had normal posture on clinical evaluation and had absence of syndesmophytes on plain radiographs. All patients were Caucasians of Northern European Ancestry. Genome-wide DNA methylation profiling was performed on the blood DNA samples from 23 AS patients with advanced ankylosis and 25 patients with no syndesmophytes. The profiling was performed using Illumina HumanMethylation450k Beadchip, which measures up ∼480, 000 different CpG sites per sample and covers 96% of RefSeq genes. The methylation level at each CpG site was measured by β values varying from 0 (no methylation) to 1 (100% methylation). Results: Advanced ankylosis patients were predominantly males (22/23), with mean of disease onset at age 21.9 years and age at time of assessment was 43.72. Meanwhile, AS patients with no syndesmophytes were also predominantly males (24/25), with mean of disease onset at age 24.6 years and age at time of assessment was 44.1 years. Methylation data were normalized using BMIQ method and no batch effects were detected by PCA analysis. Methylation analysis was performed on 382, 232 autosomal CpG sites after quality controls. One outlier was identified and excluded in the subsequent analysis. Analysis revealed 100 locations where there was a difference between patients with and without spinal ankylosis. The three locations that differentiated the most included CPG sites in KIAA0319 (hypomethylated) (p=1.7×10 -5 ); JAKMIP3 (p=6.4×10 -5 ) and LYG2 (p=9.6×10 -4 ). Based on functional relevance to AS pathogenesis, particularly antigen presentation, cytokine signalling, and bone remodeling, 5 candidate genes (4 hypomethylated; 1 hypermethylated) emerged: IL18RAP (beta diff=-0.1473; p=0.01), SMAD3 (beta diff=-0.16664; p=0.047), MCF2L (beta diff=-0.10894; p=0.009), DDAH2 (beta diff=0.11494; p=0.007), and NLRC5 (beta diff=-0.11542; p=0.052). Conclusions: These preliminary results demonstrate that the global DNA methylation pattern in advanced ankylosis differs from AS patients with no spinal damage. High priority candidate genes identified in this study warrants further validation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3270